A hidden champion? The European Court of Justice as an agenda-setter in the case of posted workers - Alexis Lubow; Susanne K. Schmidt (Public Administration, 2021)
Since the comparative turn in European integration research, analyses of the legislative process of the EU have taken inspiration from research on national political systems. While the consequences of the formal monopoly of initiative of the Commission are much analysed, it is only recently that the role of the Court in EU legislation has been further appreciated. In the literature, it is disputed how far case law constrains the EU legislator. The analysis of the 2016 proposal for a revision of the 1996 Posted Workers Directive allows us to uncover the mechanisms by which the European judiciary shapes and constrains agenda-setting based on the constitutionalization of EU law. In this highly political case, being hailed as a major breakthrough, we ask whether political majorities or case law constraints had the upper hand.
Keywords: 340